POSTSCRIPT ON SOUTH AFRRICA'S FIRST ANTI-AIRCRAFT GUNS - Bisset, W.M. (Scientia Militaria - South African Journal of Military Studies, 2012)
One of the most fascinating things about South Africa's military history is the often surprising nature of some of its sources. In a short article on South Africa's first anti-aircraft guns which appeared in Militaria 8/1, 1978 pages 22-23 the present writer mentioned that he was unable to explain why the fact that two 15-pounder BlC's had been converted to anti-aircraft guns had been given wide publicity or why it had been necessary to undertake their conversion when the Cape Peninsula seemed beyond the range of enemy aircraft.